ITI choice for the optimal management of inhibitor patients – from a clinical and pharmacoeconomic perspective. (September 2014) - Oldenburg, J.; Austin, S. K.; Kessler, C. M.
Summary: The development of alloantibody inhibitors against factor VIII (FVIII) represents the most significant complication of haemophilia care. Inhibitors tend to develop early in the course of treatment in about 20–30% of patients with severe haemophilia who receive on‐demand or prophylactic FVIII therapy. Many factors are associated with inhibitor formation, including disease severity, major FVIII gene defects, family history and non‐Caucasian race, as well as age at first treatment, intensity of early treatment, use of prophylaxis and product choice. As these latter treatment‐related variables are modifiable, they provide opportunity to minimize inhibitor incidence at the clinical level. Data from the Bonn Centre in Germany have indicated an overall success rate of 78% for immune tolerance induction (ITI) therapy, with a failure rate of 15% and with some treatments either ongoing (3%) or withdrawn (4%). Similarly, data from the G‐ITI study, the largest international multicentre ITI study using a single plasma‐derived (pd) FVIII/von Willebrand factor (VWF) product, have demonstrated success rates (complete and partial) in primary and rescue ITI of 87% and 74%, respectively, with 85% of poor prognosis patients achieving success. Favourable clinical results based on success rates and time to tolerization continue to be reported for use of pdFVIII/VWF in ITI, with pdFVIII/VWF having a particular role in patients who require rescue ITI and those with a poor prognosis for success. Data from prospective, randomized, controlled clinical studies, such as RES.I.ST (Rescue Immune Tolerance Study), are eagerly awaited. Another factor to consider with ITI therapy is cost; preliminary data from an updated decision analytic model have provided early evidence that ITI has an economic advantage compared with on‐demand or prophylactic therapy.